Radical-in-chief : Barack Obama and the untold story of American socialism - Kurtz, Stanley N. (New York : Threshold Editions, 2010)
Journalist Stanley Kurtz examines the politics of Barack Obama, focusing on his alleged socialist convictions, and suggesting that Obama's visions for the United States and long-term strategy are influenced by connections to radical groups and the Socialist Scholars Conferences.
Preface: What on earth is a community organizer? -- The socialism puzzle -- A conference for Marx -- From New York to Havana -- Obama's organizing : the hidden story -- The Midwest Academy -- ACORN -- Ayers and the foundations -- Jeremiah Wright -- State Senate years -- The Obama administration.
Keywords: Obama, Barack -- Political and social views; Radicalism -- United States; Socialism -- United States; Presidents -- United States; Legislators -- Illinois; Political activists -- Illinois -- Chicago; Community organization -- Chicago, Illinois -- History -- 20th century; United States -- Politics and government -- 2009-; Illinois -- Politics and government -- 1951-; Chicago (Ill.) -- Social conditions -- 20th century